The Theme of Violence against Children in the Daily Paper “Lietuvos rytas” (year 2002) - Dabkevičiūtė, Lina (Sociologija. Mintis ir veiksmas, 2003)
It is hard to analyse a theme about violence against children because of the lack of the trustworthiness data, which reflect the real situation. The statistics we have at present day reflect only cases, which come to light. Because of this situation the only source of knowledge – mass media. The themes of articles, their size, the style of writing and intensity control the thought of society and form a public criminal discourse, which is often based on myths, stereotypes and opinions. Mass media gives us distorted view of real situation. This article analyses what view of violence against children presents Lithuanian press, concretely daily paper “Lietuvos rytas”.